PENINGKATAN KAPASITAS KEMAMPUAN MENULIS KARYA TULIS ILMIAH BERSTANDAR JURNAL ILMIAH NASIONAL BEREPUTASI MENGGUNAKAN APLIKASI SITASI ILMIAH MENDELEY - Muhammad Junaedi; Khairul Khalqi; Soufa Malita; M Zainul Hafizi (LPPM Institut Pendidikan Nusantara Global, 2025)
Writing ability is an essential academic skill in higher education because it serves as a means to communicate ideas, construct logical arguments, and produce credible and accountable scholarly works. The national standards for scientific writing are a set of formal guidelines that regulate the structure, language rules, writing format, academic ethics, as well as citation and referencing procedures to ensure academic quality, scientific integrity, and consistency in every scholarly work produced. Mendeley is one of the reference management applications used to organize bibliographies, store scientific articles, generate automatic citations, and assist researchers in formatting references according to the required style. The enhancement of writing skills through the use of Mendeley is based on the needs of students in completing their final assignments at the university. This activity is implemented through four stages: planning, implementation, evaluation, and program sustainability. During the implementation stage, the program includes workshops on utilizing the Mendeley application, training in searching for scientific references, and hands-on practice using the application. The success of the program is evaluated by assessing students’ responses to the use of Mendeley through questionnaires and analyzing their feedback regarding the program activities. The results indicate that students have a positive perception of using Mendeley, with an average score of 90.8%, while their response to the implementation of the program reaches 85.7%.